ON THE PSYCHOLOGICAL CRITERIA AND ORIGINAL FACTORS OF DISPUTES BETWEEN YOUNG PEOPLE (Archive of Conferences, 2021)
This article describes the conflicts that occur during adolescence, the factors that cause them, the emergence of conflicts of interest, needs, views between the parties in interpersonal relationships and the emergence of conflicts based on these conflicts, as well as social tensions.